VALUASI PENGGUNAAN INTEGRATED MANAGEMENT OF CHILDHOOD ILLNESS COMPUTERIZED ADAPTATION AND TRAINING TOOL (ICATT) OLEH MAHASISWA FAKULTAS KEDOKTERAN TINGKAT KEPANITERAAN - , Diatrie Anindyajathi, Prof. dr. Srisuparyati Soenarto, Ph.D., Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: As on of the strategies in lowering the under five mortality rate, Integrated Management of Childhood Illness are being taught in pre service and in service training. From the recent evaluation of IMCI pre service training in fifteen Indonesian medical schools, factors such as lack of IMCI instructors, fund, and teaching materials seem to constrain the pre service training. IMCI Computerized Adaptation Tool (ICATT) is a computer software that may indeed be the solution of problems faced by providers in pre service training. Objective: To know the effect of ICATT in increasing the medical students' knowledge of IMCI and knowledge of child health in general. Method: This quasi-experimental study compared the pre and post test scores of medical students' knowledge of IMCI. We also compared the mean OSCE (Objective Structured Clinical Examination) of students given ICATT and students that were not given ICATT. Focus group discussions were done to identify the students' perception of ICATT and portray students' learning process of ICATT. Result: Students that were given ICATT showed a higher post test of IMCI knowledge compared to pre test (p<0.05